1986
DOI: 10.1093/geronj/41.6.793
|View full text |Cite
|
Sign up to set email alerts
|

Widowhood, Sex, Labor Force Participation, and the Use of Physician Services by Elderly Adults

Abstract: This paper investigated the relationships of widowhood, sex, and labor force participation with the use of ambulatory physician services by elderly adults. Data on 18,441 individuals aged 55 and over were taken from the 1978 Health Interview Survey. Hierarchical regression results indicated that although these three factors are related to physician utilization at the zero- and first-partial levels, only sex remained significant when their two- and three-way interactions and other variables from the behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Demographic characteristics (age, gender, race) are attributes of an individual corresponding to vital statistics. Results of previous studies show that older, white (Lefkowitz & Monheit, 1991), and female elders (Homan, Haddock, Winner, Coe, & Wolinksy, 1986;Short & Leon, 1990) were most likely to use in-home and community services and, specifically, transportation services (Iutcovich & Iutcovich, 1988;Smith & Hiltner, 1988). Contrary to these findings, Wolinsky and Johnson ( 199 1) reported age, gender, and race were not predictors of service use.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Demographic characteristics (age, gender, race) are attributes of an individual corresponding to vital statistics. Results of previous studies show that older, white (Lefkowitz & Monheit, 1991), and female elders (Homan, Haddock, Winner, Coe, & Wolinksy, 1986;Short & Leon, 1990) were most likely to use in-home and community services and, specifically, transportation services (Iutcovich & Iutcovich, 1988;Smith & Hiltner, 1988). Contrary to these findings, Wolinsky and Johnson ( 199 1) reported age, gender, and race were not predictors of service use.…”
mentioning
confidence: 98%
“…Medicaid eligibility, though, was not associated with the probability of receiving in-home services (Kemper, 1992). Low income elders were more likely to use transportation services than elders with moderate or high income (Iutcovich & Iutcovich, 1988;Smith & Hiltner, 1988); higher income was associated with greater likelihood of community-based services (Mui & Burnette, 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers based this conclusion on the fact that more widows live alone and are less likely to work compared to widowers. Further, the researchers found that an individual will use more health services if they live alone and are not in the labor force compared to an individual who lives with others and is in the labor force (Homan, et al, 1986). In other research on self-rated health assessment, Choi (1996) found that marital status was not a significant determinant of self-assessment of health status, all other things being equal.…”
Section: Elder Populationmentioning
confidence: 93%
“…Specifically, Goldman, et al, (1995) found an unanticipated result; among older non-married there were "variations in health outcomes across the three [nonmarried] groups." However, results from research investigating the relationship between widowhood, gender and labor force participation with ambulatory physician service utilization suggests that "the effects of widowhood and labor force participation are spurious" (Homan, et al, 1986). The researchers based this conclusion on the fact that more widows live alone and are less likely to work compared to widowers.…”
Section: Elder Populationmentioning
confidence: 99%